2017
DOI: 10.14475/kjhpc.2017.20.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Change in Palliative Performance Scale (PPS) Predicts Survival in Patients with Terminal Cancer

Abstract: Purpose:The Palliative Performance Scale (PPS) is a widely used prognostic tool in patients with advanced cancer. This study examines the association between changes in PPS score and survival in patients with advanced cancer. Methods: We identified a cohort of 606 inpatients who died at a Korean university hospital's hospice/palliative care center. For each patient, the PPS score was measured twice according to a standard procedure: 1) upon admission, and 2) three days after admission (D3). "Change on D3" was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…One study among hospitalized patients with terminal cancer identified a score change of >30% yielded a HR for death of 2.66 (95% CI: 2.19-3.22) compared to a score change of ≤30% [23]. A PPS score of ≤30 was also independently predictive of survival with a HR of 1.67 (95% CI: 1.30-2.02) compared to a PPS score >30 [28]. Where our investigation noted a single PPS score at the time of admission, changes in PPS may be a more sensitive indicator of death.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…One study among hospitalized patients with terminal cancer identified a score change of >30% yielded a HR for death of 2.66 (95% CI: 2.19-3.22) compared to a score change of ≤30% [23]. A PPS score of ≤30 was also independently predictive of survival with a HR of 1.67 (95% CI: 1.30-2.02) compared to a PPS score >30 [28]. Where our investigation noted a single PPS score at the time of admission, changes in PPS may be a more sensitive indicator of death.…”
Section: Discussion/conclusionmentioning
confidence: 99%